ANALYSIS OF SERVANT LEADERSHIP, ORGANIZATION CULTURE ON EMPLOYEE PERFORMANCE WITH ORGANIZATION COMMITMENT AS AN INTERVENING VARIABLE AT THE TAX SERVICE OFFICE OF ACEH PROVINCE - Krismiyanto; Herman Fithra; Marbawi (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
This study aims to analyze the influence of Servant Leadership, Organization Culture on Employee Performance with Organization Commitment as an Intervening Variable at the Tax Service Office of Aceh Province, the dependent variable of this study is servant leadership and the organization culture for the independent variable is employee performance, for the intervening variable is organizational commitment. The population in this study is 265 personnel from the Tax Service Office of Aceh Province. The sampling technique used proportionate stratified random sampling and a sample of 170 respondents who were employees at the Tax Service Office of Aceh Province was obtained, the research method used was a quantitative method, for the data analysis method using Structural Equation Modeling (SEM). The results of this study show that servant leadership and organizational culture have a significant effect on organizational commitment, further servant leadership, organizational culture and organizational commitment have a significant effect on the performance of employees of the Aceh Provincial Tax Service Office. This study shows that organization commitment is the most dominant variable affecting the performance of employees of the Tax Service Office of Aceh Province. In this study, servant leadership and organization culture have a significant effect on employee performance through organization commitment as an intervening variable, it can be concluded that organizational commitment functions as a partial mediation between exogenous and endogenous variables.